If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 27 = -72 Reorder the terms: 27 + 9y = -72 Solving 27 + 9y = -72 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 9y = -72 + -27 Combine like terms: 27 + -27 = 0 0 + 9y = -72 + -27 9y = -72 + -27 Combine like terms: -72 + -27 = -99 9y = -99 Divide each side by '9'. y = -11 Simplifying y = -11
| -x/2+3=-12 | | 92=6(r+2)+4r | | 3y-1/2=z | | 90=6(3x+1)-6x | | 5x-12+3x+6=72 | | -40+8=-10+-24 | | 4x^6-3y^4+6x^6+6y^4= | | -2=5+1x | | x/3-9=10 | | 2t+3+3t-4t=4+2 | | 4x^6-3y^4+6x^6y^4-6x^6+6y^4= | | -x-2=6 | | x/2-13=11 | | -53+29=x | | x^2+16=-5 | | -53+23=x | | -53+=x | | 5x^2+5y^2=25 | | a=36-cforb | | 3x+12=-18x-9x+1 | | -53+29= | | 5.35=2.37 | | -2+8=-20 | | 2x+14=15x-10 | | 4.8x-3=3.8 | | 3/x+2=6/x-5 | | -2=14 | | 4(x-3)+y=21 | | 9z+12=9-3z | | 1/2x=100 | | 2x-1/y=w+2/2z | | 2(m+3)+5m=-3 |